The diagnostic accuracy of the Forns index, platelet count and AST to Platelet Ratio Index derived fibrosis index for the prediction of Hepatitis C virus-related significant liver fibrosis and cirrhosis. (April 2014) - Kayadibi, Huseyin; Yasar, Bulent; Ozkara, Selvinaz; Serdar, Muhittin A.; Kurdas, Oya O.; Gonen, Can
Abstract Aim. To provide a simple fibrosis index combining the routine laboratory markers for predicting significant fibrosis (SF) and cirrhosis in patients with chronic HCV. Methods. Platelet count, ALT, AST, AST to ALT Ratio, AST to Platelet Ratio Index (APRI), Forns index, FIB-4 and Age Platelet Index of 202 liver biopsy performed HCV-infected patients were reviewed. METAVIR classification was used to determine the stage of liver fibrosis. The predictive fibrosis index was constructed by multiple linear regression analysis (− 2.948 + 0.562 × Forns index + 0.288 × APRI + 0.006 × platelet count [109/L]). Results. Median (25th–75th interquartile range) age was 52 (42–59) years, and 61% were male. 65.8% (n = 133) had SF (F2–F4) and 23.3% (n = 47) had cirrhosis (F4). For discrimination of SF, AUROCs were: Fibrosis index = 0.869, Forns index = 0.837, APRI = 0.814, platelet count = 0.764. For cirrhosis, AUROCs were: Fibrosis index = 0.911, Forns index = 0.883, APRI = 0.847, platelet count = 0.827. A cut-off point of ≤ 1.2 for fibrosis index excluded SF in 89% of patients with sensitivity of 96%, while > 2.0 predicted SF in 88% of patients with specificity of 86%. Threshold of ≤ 1.9 excluded cirrhosis in 95% of patients with sensitivity of 94%, while > 2.7 showed cirrhosis in 88% of patients with specificity of 95%. In multivariate logistic regression analysis, OR (95% CI) of fibrosis index was 7.825 (3.682–16.629) for SF (p < 0.001) and was 8.672 (4.179–17.996) for cirrhosis (p < 0.001). Conclusion. SF and cirrhosis were predicted with accuracy of 82% and 89% and were excluded with accuracy of 74% and 82% using this fibrosis index which may potentially decrease the need for liver biopsy in 76% and 83% of patients, respectively.